LAW AND INTERNATIONAL CRIMES - Płosa, Tomasz; Iwan-Sojka, Dominika (No Limits, 2022)
Everything that has been happening in Ukraine since 24 February 2022 fills us with horror, compassion, and moral objection. There is no doubt that Putin, his closest associates, the commanders of the Russian army, and its regular soldiers are responsible for the evil that is taking place in our neighbour’s territory. The tragedy of the Ukrainian people demands justice and just punishment for the culprits. However, let us try to disconnect emotionally and analyse the current situation in Ukraine in the context of international law.